2022
DOI: 10.1371/journal.pone.0266562
|View full text |Cite
|
Sign up to set email alerts
|

Distressed Democrats and relaxed Republicans? Partisanship and mental health during the COVID-19 pandemic

Abstract: The COVID-19 pandemic was a potent stressor, yielding unprecedented levels of mental distress. However, public health responses and personal reactions to the pandemic were politically polarized, with Democrats highlighting and Republicans downplaying its severity. Did Republicans subsequently experience as much mental distress as Democrats during the COVID-19 pandemic? This study examines partisan patterns in mental health outcomes at three time points throughout the pandemic. Results demonstrate a clear parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Although increased stress during the COVID-19 pandemic was a common phenomenon across the US, the increase differed between political groups. xvi Bock and Schnabel (2022) found a partisan distress gap, with Democrats reporting higher levels of distress than Republicans did. xvii Additionally, Calvillo, Ross, Garcia, Smelter, and Rutchick (2020) argued that there was a difference in the coverage of the pandemic between the media platforms of the different parties, with Democratic media emphasizing the severe risk of the pandemic, while Republican media were more sceptical of the risk.…”
Section: Stress and The Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Although increased stress during the COVID-19 pandemic was a common phenomenon across the US, the increase differed between political groups. xvi Bock and Schnabel (2022) found a partisan distress gap, with Democrats reporting higher levels of distress than Republicans did. xvii Additionally, Calvillo, Ross, Garcia, Smelter, and Rutchick (2020) argued that there was a difference in the coverage of the pandemic between the media platforms of the different parties, with Democratic media emphasizing the severe risk of the pandemic, while Republican media were more sceptical of the risk.…”
Section: Stress and The Covid-19 Pandemicmentioning
confidence: 99%
“…Republicans report much better mental health than others, Gallup Poll. xvii See Bock and Schnabel (2022). xviii See Calvillo, Ross, Garcia, Smelter, and Rutchick (2020).…”
mentioning
confidence: 99%
“…Higher risk perceptions in turn translated into more negative emotion and greater stress. Data collected between May and August of 2020 showed that Democrats consistently reported stronger negative emotions and higher levels of stress than Republicans (Bock & Schnabel, 2022 ). This is also consistent with evidence that, compared to Democrat‐trusted media, right‐wing media tended to promote misinformation that downplayed the severity of the pandemic and expressed more positive sentiment in their coverage of COVID‐19 (Guntuku et al., 2021 ; Lau et al., 2022 ; Motta et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%